2004
DOI: 10.1128/cdli.11.2.387-391.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin M Antibody Responses toMycobacterium ulceransAllow Discrimination between Cases of Active Buruli Ulcer Disease and Matched Family Controls in Areas Where the Disease Is Endemic

Abstract: Buruli ulcer disease (BUD) is an emerging disease caused by, and the specificity determined with sera from family controls was 95.5% (95% CI, 87.5 to 98.4%). These studies suggest that the IgM responses of patients with BUD will be helpful in the identification and production of the M. ulcerans recombinant antigens required for the development of a sensitive and specific serological assay for the confirmation of active BUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In tuberculosis (Tb) endemic areas, where BCG vaccination is common, the broad antigenic cross-reactivity of M. ulcerans antigens with M. tuberculosis and M. bovis antigens complicate the analysis of M. ulcerans specific immune responses substantially. In studies with M. ulcerans culture filtrates IgG antibody responses against the secreted M. ulcerans proteins were frequently found in BU patients, but also in Tb patients from BU non-endemic regions [75,76] . IgM responses of BU patients against the filtrate proteins were more distinct than those of healthy family members living in the same village [76] , indicative for B cell stimulation.…”
Section: Histopathologic Features Of Untreated Buruli Ulcer Lesionsmentioning
confidence: 98%
“…In tuberculosis (Tb) endemic areas, where BCG vaccination is common, the broad antigenic cross-reactivity of M. ulcerans antigens with M. tuberculosis and M. bovis antigens complicate the analysis of M. ulcerans specific immune responses substantially. In studies with M. ulcerans culture filtrates IgG antibody responses against the secreted M. ulcerans proteins were frequently found in BU patients, but also in Tb patients from BU non-endemic regions [75,76] . IgM responses of BU patients against the filtrate proteins were more distinct than those of healthy family members living in the same village [76] , indicative for B cell stimulation.…”
Section: Histopathologic Features Of Untreated Buruli Ulcer Lesionsmentioning
confidence: 98%
“…The test should discriminate between immune responses against M. ulcerans and other mycobacteria, in particular M. tuberculosis and M. bovis BCG. Serological studies performed with complex antigen preparations have suggested that serological tests may be useful in the diagnosis and surveillance of Buruli ulcer (9,16,31). In view of the presence of species cross-reactive antibodies in sera of Africans living in regions where Buruli ulcer is endemic, thoroughly selected recombinantly expressed target antigens are required.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Strong IgM antibody responses to M ulcerans seem more frequent in patients with active Buruli ulcer than in healthy members of their families. 26 HIV infection Review has not been reported as a risk factor for Buruli ulcer 27 but severe clinical forms of the disease have been described in HIV-positive patients. 28 In three HIVpositive Buruli ulcer patients in Akoloninga, Cameroon, we observed that the healing process improved when the patients started antiretroviral treatment (EC, unpublished data).…”
Section: Figure 1: a Typical Buruli Ulcermentioning
confidence: 99%